1996
DOI: 10.1016/0014-5793(96)00643-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA initiates polymorphic structural transitions in lecithin

Abstract: • ~,'ey words." DNA-lipid interaction; Transfection; 1 ipid polymorphism; Membrane ultrastructure Materials and methods Preparation of complexCalf thymus DNA was purchased from Sigma, additionally purified using phenol and chloroform (A26olA2so value being greater than 1.9) and mildly ultrasonicated until the formation of rather homogeneous native fragments with a chain length of about 300-500 bp. The DNA fragments were mixed with a 1 mg/ml suspension of sonicated small unilamellar vesicles of egg PC or DPPC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 25 publications
6
49
0
1
Order By: Relevance
“…It has been shown that such an organization can induce the formation of a very clustered form of DNA (40). Studies on model membrane systems showed that DNA-lipid complexes could be formed under different conditions bringing DNA interfacial accumulation (41,42). The local interfacial high concentration of DNA induced an electrostatic segregation of the cationic lipids and a compaction of the outer layer (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that such an organization can induce the formation of a very clustered form of DNA (40). Studies on model membrane systems showed that DNA-lipid complexes could be formed under different conditions bringing DNA interfacial accumulation (41,42). The local interfacial high concentration of DNA induced an electrostatic segregation of the cationic lipids and a compaction of the outer layer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Electron freeze fracture micrographs of aggregates of DNA formed with natural egg yolk phosphatidylcholine (EYPC) and synthetic saturated DPPC in presence of Ca 2+ cations suggested structures with long-range organization. The honeycomb-like and spaghetti-like structures were observed in EYPC+DNA+Ca 2+ aggregates (Tarahovsky et al, 1996), while structures formed in presence of DPPC were identified either as sandwich or spaghetti-like, depending on the DNA base:DPPC molar ratio . Small-angle X-ray diffractograms show two possible structural organizations of DPPC+DNA+divalent cation aggregates: We identified a sandwich structure in the aggregate DPPC:DNA:Mg 2+ =1:1:5 mol/base/mol in the temperature range 20-60°C, with a lipid bilayer repeat distance d~8.0-7.6 nm and interhelical DNA -DNA distance d DNA~6 .4-6.0 nm (Uhríková et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…However, complexes composed entirely of natural, zwitterionic lipid can complex with DNA when the interaction is mediated by a divalent cation. [9][10][11][12][13][14] Complexes formed by neutral lipids in the absence of the divalent cation have also been described. 15,16 The divalent cation-lipid complexes are entirely noncytotoxic and thereby have a remarkable status among the candidate systems in that the binding is highly tunable.…”
mentioning
confidence: 99%